The Spatial Construal of TIME in Indonesian: Evidence from Language and Gesture - Gede Primahadi Wijaya Rajeg; Poppy Siahaan; Alice Gaby (Masyarakat Linguistik Indonesia, 2022)
This paper presents evidence from language and gesture for the spatial conceptualisation of time in Indonesian. Linguistic evidence corroborates the dominant patterns of space-time mapping for deictic (i.e., future, present/now, and past) and sequential times (i.e., before-after). Indonesian speakers talk about the future as an event in front of the Ego, while the past is behind the Ego. The spontaneous gestural data reflect and extend the patterns observed in other languages. Forward and backward (i.e., sagittal) gestures tend to accompany future and past expressions respectively. Deictic times can also be construed through the leftward and rightward (i.e., lateral) gestures and the combination of the sagittal and lateral axes, which lack a linguistic analogue. The sequential-time gesture is more likely to be lateral. Our study contributes to (i) the exploration of universality and variation in the construal of time in language and gesture, and (ii) the growing interest within Cognitive Linguistics in converging and/or diverging evidence from different methods and data types.